2017
DOI: 10.4049/jimmunol.1601335
|View full text |Cite
|
Sign up to set email alerts
|

TLR10 Is a B Cell Intrinsic Suppressor of Adaptive Immune Responses

Abstract: Toll-like receptors (TLRs) play a central role in the initiation of adaptive immune responses with several TLR agonists acting as known B-cell mitogens. Despite thousands of publications on TLRs, the function of TLR10 remains unknown. We have found that antibody mediated engagement of TLR10 on primary human B-cells suppresses B-cell proliferation, cytokine production and signal transduction. When challenged with either a T-independent or T-dependent antigen, TLR10 transgenic mice exhibit diminished antibody re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…8a ). At the single cell level, we observed that TLR10 was only expressed by HLA + B cells, indicating that TLR10 has a functional role within the B cell lineage 36 . In contrast, TLR8 was significantly elevated in all RA monocyte subsets.…”
Section: Resultsmentioning
confidence: 88%
“…8a ). At the single cell level, we observed that TLR10 was only expressed by HLA + B cells, indicating that TLR10 has a functional role within the B cell lineage 36 . In contrast, TLR8 was significantly elevated in all RA monocyte subsets.…”
Section: Resultsmentioning
confidence: 88%
“…TLR10 is structurally similar to the other TLR family members and is phylogenetically most related to TLR1 and TLR6. 3 TLR10 mRNA is highly expressed in lymphoid tissues, 3 and is expressed in different immune cells, including B cells, dendritic cells, [4][5][6] and monocytes. 4,7 Currently, there is no natural ligand identified for TLR10.…”
Section: Introductionmentioning
confidence: 99%
“…TLR10 remains an orphan receptor without a confirmed ligand, signaling pathway, or biological function. However, it is widely expressed in lymphoid tissues including the spleen, lymph node, thymus, and tonsils as well as a number of leukocyte subtypes, especially B cells ( 13 ). This expression pattern suggests that TLR10 has an immune function similar to other TLRs.…”
Section: Introductionmentioning
confidence: 99%